Low Resighting Rate of Entangled Humpback Whales Within the California, Oregon, and Washington Region Based on Photo-Identification and Long-Term Life History Data - Tackaberry, Jennifer; Dobson, Elana; Flynn, Kiirsten; Cheeseman, Ted; Calambokidis, John (Frontiers in Marine Science, 2022)
Bycatch, commonly referred to as entanglement, is a leading source of human-caused mortality of baleen whales. A better understanding of the individuals that survive (or perish from) their entanglement can help reduce the risk of bycatch by informing gear modifications and fisheries management. However, determining survival rates is restricted by the ability to track individuals once they become entangled. Historically, the effort to identify and resight individuals from known entanglement cases was low along the West Coast. The recent increase of entanglements and photo-identification efforts in the California, Oregon, and Washington region provides an opportunity to assess entangled humpback whales’ resighting rates to better understand the effect of entanglements from the individual to the population level. We used photo-ID images of entangled humpback whales between 1982 and 2017 to examine pre- and post-entanglement sighting histories from longitudinal catalogs and life history data (Cascadia Research and Happywhale). We compared the entangled whales (n = 37) against control whales (n = 2,296), selected based on the date and location of the entanglement reports, to evaluate the deviation from the expected mortality rates (or lack of resighting) caused by entanglements and to help inform/support/test National Oceanic and Atmospheric Association’s Serious Injury and Mortality (SI/M) index. Our results suggest that entangled whales were resighted less often than the control groups. Entangled whales with short pre-entanglement sighting histories and without post-entanglement resights did not match other feeding ground populations. Therefore, the higher proportion of entanglements with shorter sighting histories is likely due to their being alive for fewer years, indicating a higher risk of entanglement for younger whales. This indicates that entangled humpback whales may not be as large or strong as mature individuals, and future gear modifications should reflect that possibility. Additionally, the severity of the initial SI/M score aligned well with our resighting rates, though this worsened with the final score assigned. Continued effort to gather and improve data collection about entanglements will help enhance the SI/M determinations. Our findings show the value of photo-identification of entangled whales and how it dramatically increases our understanding of entanglements.